La consulta a los pueblos indígenas y su evolución como herramienta de negociación política en América Latina. Los casos de Perú y Guatemala - Fulmer, Amanda M. (2011)
This article analyzes the right to consultation, guaranteed to indigenous peoples by ILO Convention 169, in its social, cultural, legal and political context. I draw on two case studies, one in Peru (the Rio Blanco case) and one in Guatemala (the Marlin mine case). Consultation has been an important element of both cases, but has played a different role in the two cases. Based on sixteen months of research in both countries, I argue that the right to consultation has been important for indigenous mobilization, primarily as a symbolic tool of legitimation, and less so as a legal mechanism.